KOMUNIKASI PARIWISATA E-TOURISM - Indah Sari Oktavianti; Wa Ode Nurul Yani (Dialektika, 2017)
This study aims to determine the E -Tourism Communication Tourism Lombok Island. Travelers who studies Conducting In-depth Interviews Ticket Booking Online Using a Website Lombok Network Holidays Tours and Travel. This study used a qualitative research method, the research paradigm of constructivism, and in-depth interview study research approach. Subjects of the study were purposively determined travelers based communication problems of-tourism in Lombok Island. The process of data collection was obtained through in depth interviews and observations as well as the role of the informant, while supporting data obtained through documentation of the results of previous research studies, and other literature, as well as interviews with relevant parties. The results showed that the e -tourism in tourism communication is impersonal means of communication which includes advertising, sales promotion, and public relations dikonvergensikan (combined) in a media online network of -tourism which consists of a websit , blog and social media can be used to provide information to the world on the island of Lombok attractions. E-tourism benefit the countries where people are already aware of the media (media literacy, but for countries where people have not been aware of the media or have not used in an optimal network media, it can be difficult for foreign tourists because tourism is difficult to acces, accommodation and tourism travel agent. Without e -tourism, local tourism travel agency can not promote their business activities and the lack of government and public opinion of the original potential of the tourism sector. Indonesian society is still much to worry about to book tickets online.